Thermal ecosystem engineering by songbirds promotes a symbiotic relationship with ants - Marta Maziarz (Nature Portfolio, 2020)
Abstract Nesting birds can act as thermal ecosystem engineers by providing warm habitats that may attract arthropods to colonise the nest structure. This cohabitation of birds and nest-dwelling invertebrates may foster symbiotic relationships between them, but evidence is lacking. We investigated whether ants are attracted to bird nests by the heat generated by the hosts, and/or the nests’ structural insulation properties, to raise their broods (larvae and/or pupae) in advantageous thermal conditions. We found that the endothermic activity of birds within their nests created ‘heat islands’, with thermal conditions potentially promoting the survival and development of ant larvae in cool environments. We experimentally confirmed that the presence of heat within bird nests, and not the structure itself, attracted the ants to colonise the nests. As ants might benefit from exploiting warm bird nests, this may be a previously overlooked commensal, mutualistic or parasitic relationship which may be ecologically significant and globally widespread among various nesting birds and reproducing ants. Similar interspecific interactions may exist with other arthropods that reproduce in avian and mammalian nests. Further research is needed to reveal the nature of these relationships between such taxa, and to understand the role of warm-blooded animals as thermal ecosystem engineers.